HypoxamiRs and Cancer: From Biology to Targeted Therapy - Gee, Harriet E. (Mary Ann Liebert, Inc., 2014)
Significance: Hypoxia is a hallmark of the tumor microenvironment and represents a major source of failure in cancer therapy. Recent Advances: Recent work has generated extensive evidence that microRNAs (miRNAs) are significant components of the adaptive response to low oxygen in tumors. Induction of specific miRNAs, collectively termed hypoxamiRs, has become an accepted feature of the hypoxic response in normal and transformed cells. Critical Issues: Overexpression of miR-210, the prototypical hypoxamiR, is detected in most solid tumors, and it has been linked to adverse prognosis in many tumor types. Several miR-210 target genes, including iron-sulfur (Fe-S) cluster scaffold protein (ISCU) and glycerol-3-phosphate dehydrogenase 1-like (GPD1L), have been correlated with prognosis in an inverse fashion to miR-210, suggesting that their down- regulation by miR-210 occurs in vivo and contributes to tumor growth. Additional miRNAs are modulated by decreased oxygen tension in a more tissue-specific fashion, adding another level of complexity over the classic hypoxia-regulated gene network. Future Directions: From a biological standpoint, hypoxamiRs are emerging modifiers of cancer cell response to the adaptive challenges of the microenvironment. From a clinical perspective, assessing the status of these miRNAs may contribute to a detailed understanding of hypoxia-induced mechanisms of resistance and/or to the fine-tuning of future hypoxia-modifying therapies. Antioxid. Redox Signal. 21, 1220–1238.